Role of fully-immersive virtual reality for paretic arm recovery in stroke rehabilitation - Shin, Seyoung; Hwang, Gyoseok; Kim, Yubin; Park, EunYoung; Cho, Dong Rae; Baik, Hongsuk; Kim, MinYoung (Frontiers in Neurology, 2025)
IntroductionRehabilitative training using fully immersive virtual reality (VR) has emerged as a promising method for improving motor function in patients with stroke. We evaluated the efficacy of VR technology as an adjunctive therapy in stroke rehabilitation.MethodsA VR program was designed by the research team to facilitate the movement of the paralyzed arm, and participation was offered to inpatients on a voluntary basis at a university-affiliated Rehabilitation Medicine Center. A retrospective analysis was conducted on patients with subacute stroke who were selected without bias between November 2015 and January 2020. Clinical outcomes were compared between the VR-received (n = 30) and the control groups (n = 14), which received only conventional rehabilitation. Outcome measures included the Fugl–Meyer Assessment for Upper Extremity, modified Barthel Index, Functional Independence Measure, Mini-Mental Status Examination, and Motor-Free Visual Perception Test, performed before and after each treatment, and changes in the scores between the two time points were measured. A subgroup analysis was conducted according to the number of VR interventions in the VR group. Multivariate regression was used to control for confounding variables.ResultsThere were no significant differences in baseline demographic characteristics and functional abilities between the two groups, except for a longer interval between the pre- and post-assessments in the control group (p < 0.01). The VR group showed a significantly greater improvement in Fugl–Meyer Assessment for Upper Extremity scores on the affected side than the control group did (p = 0.01). Multivariate analysis identified VR intervention as an independent predictor of motor improvement (β = 15.78), whereas delayed rehabilitation onset was negatively associated with recovery (β = −0.83).ConclusionIn this case-control study, the findings suggest that incorporating fully immersive VR-based training in rehabilitation may enhance upper limb function recovery in patients with stroke in the subacute phase. Further randomized controlled studies are required to confirm these findings.